Development of a Climate Smart Financing Bundle for Wheat in Ethiopia - Wamicwe, Peter; Merbat, Wondwossen Worku; Solomon, Dawit; Tesfaye, Kindie; Heintz, Lennart; Derenoncourt, Marie Ena; Newman, Richard; Grosjean, Godefroy; Mufti, Samaa; Cosgrove, Bethany Emma; Tesfaye, Lidya; Zulu Hume, Mercy; et al. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The report aims to provide an overview of the feasibility and pre-implementation phase activities being undertaken by AICCRA under The Aggregator Growth Development & Investment Program in Ethiopia to co-design a comprehensive scalable climate-smart bundled finance solution targeting the Wheat Value Chain.